Synthesis and enhanced visible light photocatalytic activity of g- C3N4/BiOClxBr1-x heterojunctions with adjustable energy band structure. (September 2019) - Feng, Yibing; Du, Yi; Du, Minxing; Tian, Xiuying; Jiang, Nan; Liu, Yang
Abstract: The g-C3 N4 /BiOClx Br1-x heterojunctions photocatalysts with different band gaps were successfully synthesized via a simple precipitation process. The photocatalytic activitys of the g-C3 N4 /BiOClx Br1-x composites were evaluated through the degradation of Tetracycline Hydrochloride (TC) under visible light irradiation. Compared with pure g-C3 N4 and BiOClx Br1-x, the hybrids exhibited prominently enhanced visible light photocatalytic activity for the degradation of TC. The various photocatalytic perfprmances of g-C3 N4 /BiClx Br1-x heterojunctions with same content of g-C3 N4 were determined by different optical absorption capabilities resulting from the band structures, which could be controlling by changing the molar ratio of Br to Cl in BiOClx Br1-x . The 10-CN/BiOCl0·5 Br0.5 (g-C3 N4 content: 10%) showed the highest photocatalytic activity toward TC, due to the optimal synergistic effect of bandgap structure and effective separation of electron-hole pairs. Furthermore, the capture experiments of 10-CN/BiOCl0·5 Br0.5 during photocatalytic reaction were also carried out, the results indicted the holes (h + ) and superoxide radicals (-O2 - ) were the main active substances causing the enhancement of photocatalytic activity. Finally, we proposed a reasonable photocatalytic degradation of this g-C3 N4 /BiOClx Br1-x heterojunction photocatalysts. Graphical abstract: Image 1 Highlights: g-C3 N4 /BiOClx Br1−x composites were successfully synthesized and characterized. The band energy of composites can be tunable via solid-solution strategy. g-C3 N4 /BiOClx Br1-x exhibited excellent photo-activity to pure g-C3 N4 or BiOClx Br1-x . The mechanism behind the enhanced photocatalytic performance are proposed.